The scientific and technological research as an instrument of social development and agent of social inclusion - Lazzareschi, Noêmia (2007)
Underveloped technology countries bare the hard consequences of the dependence vicious circle: they are dependents because they have delayed technology and they have delayed technology because they are dependents. Only with massive investiments in school education and in scientific and technological research they should break this vicious circle, greatly responsable for the social wounds and build a new social structure in which most people, if not all their population can, in fact, to perform their citizen’s rights, putting an end to the social exclusion.